Geometric Evaluation of Bends Implications for Traffic Performance: A Systematic Literature Review - Wirdianto, Agus; Natawibawa K, Surya; Fadillah, Ahmad; Rijaluddin, Arief; Isradi, Muhammad (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Every accident that occurs inevitably involves injured or deceased victims. Cross-country analysis of accident rates at curves is often the focus of comparative research to identify risk factors and possible solutions. This study aims to systematically evaluate the implications of curve geometry design on traffic performance and driving safety. Road curves, particularly those that do not meet geometric standards, are known to be significant accident-prone areas. This study was conducted using a Systematic Literature Review (SLR) approach on 1,000 scientific articles obtained through Google Scholar using the Publish or Perish software. Analysis was conducted using VOSviewer to map keyword relationships, publication trends, and thematic classifications visually and statistically. The study results indicate that aspects such as curve radius, elevation, visibility, driver behavior, traffic signs, and environmental factors are the primary dimensions influencing curve performance. Bibliometric visualization revealed the dominance of related literature in developed countries and indicated a shift in research focus toward the use of technology and data to support safety. A conceptual framework was developed by integrating four dimensions: physical design, Environment, user behavior, and safety effectiveness. This research is expected to provide a theoretical and technical foundation for formulating safer road design standards and promoting the development of data-driven safety policies.